Photobiomodulation as an Adjunctive Treatment to Physiotherapy for Reduction of Anterior Knee Pain in Combat Soldiers: A Prospective, Double‐Blind, Randomized, Pragmatic, Sham‐Controlled Trial. Issue 10 (8th June 2021) - Gavish, Lilach; Spitzer, Elad; Friedman, Ilan; Lowe, Joseph; Folk, Nathalie; Zarbiv, Yonaton; Gelman, Evgeny; Vishnevski, Lev; Fatale, Evgeny; Herman, Michael; Gofshtein, Roni; Gam, Arnon; et al.
Abstract : Background and Objectives: Anterior knee pain (AKP) is the most common knee pathology in athletes and occurs in 15% of army recruits of elite units during basic training. Of these, 50% are symptomatic 6 years later. Photobiomodulation (PBM) is a nonthermal red‐to‐near‐infrared irradiation used for pain reduction of a variety of etiologies. This study was designed to determine whether addition of PBM to physiotherapy (PT) for AKP in combat soldiers is superior to PT alone. Study Design/Materials and Methods: In this prospective, double‐blind, sham‐controlled, randomized clinical trial (NCT02845869), 26 combat soldiers/policemen (male:female, 15:11; body mass index [BMI] = 24.2 ± 3.9, n = 46 knees), with AKP due to overuse/load, received 4 weeks of PT + sham (PT + Sham) or active PBM (wavelength = 660 and 850 nm, pulsing = 2.5 Hz, LED power = 50 mW/cm 2 [local tissue/regional lymph nodes]; 810 nm continuous beam, laser cluster 6 W/cm 2 [analgesia] and laser pointer 4.75 W/cm 2 [trigger points]) (PT + PBM). The main outcome measures were subjective pain by visual analog scale (VAS) (0 [none]–100 [intolerable]) and functional disability by Kujala score (0 [worst]–100 [best]). Evaluations were carried out at baseline, end of treatments, and 3‐month follow‐up. Results: All participants completed the treatment protocol without any reported adverse device effects. Post‐treatment pain was significantly reduced in the PT+PBM group, compared with baseline and sham (Δpain, VAS, mean ± SD: PT + PBM = −19 ± 23, P = 0.002; PT + Sham = −6 ± 21, P = 0.16; between groups, P = 0.032). At 3‐month follow‐up, pain reduction was similar between groups; however, the Kujala score was significantly improved only in the PBM‐treated group (ΔKujala: PT + PBM = 11 ± 10, P = 0.003; PT + Sham = 5 ± 7, P = 0.059). Conclusions: Addition of PBM to PT for AKP resulted in earlier reduction in pain and improved functionality, compared with PT alone. This noninvasive, nonpharmacologic, adjunctive therapeutic modality can be easily incorporated into team healthcare frameworks or end units and may lead to earlier return to competition or combat‐level service. Lasers Surg. Med. © 2021 Wiley Periodicals LLC